Mobile electroencephalography captures differences of walking over even and uneven terrain but not of single and dual-task gait - Jacobsen, Nadine Svenja Josée; Blum, Sarah; Scanlon, Joanna Elizabeth Mary; Witt, Karsten; Debener, Stefan (Frontiers in Sports and Active Living, 2022)
Walking on natural terrain while performing a dual-task, such as typing on a smartphone is a common behavior. Since dual-tasking and terrain change gait characteristics, it is of interest to understand how altered gait is reflected by changes in gait-associated neural signatures. To investigate this, 64-channel electroencephalography (EEG) of healthy volunteers was recorded while they walked over uneven and even terrain outdoors with and without performing a concurrent task (self-paced button pressing with both thumbs). Data from n = 19 participants (M = 24 years, 13 females) were analyzed regarding gait-phase related power modulations (GPM) and gait performance (stride time and stride time-variability). GPMs changed significantly with terrain, but not with task. Descriptively, a greater beta power decrease following right-heel strikes was observed an uneven compared to even terrain. No evidence of an interaction was observed. Beta band power reduction following the initial contact of the right foot was more pronounced on the uneven than on the even terrain. Stride times were longer on uneven compared to even terrain and during dual- compared to single-task gait, but no significant interaction was observed. Stride time variability increased on uneven compared to the even terrain but not during single- compared to dual-tasking. The results reflect that increases in terrain difficulty result in a slower and more irregular stride, whereas a secondary task slows stride duration only. Mobile EEG captures GPM differences linked to terrain changes, suggesting that the altered gait control demands and associated cortical processes can be identified. This and further studies may help to lay the foundation for protocols assessing the cognitive demand of natural gait on the motor system.